Diagnóstico patológico e laboratorial da infecção pelo vírus da língua azul (Bluetongue) em ovinos no sul de Minas Gerais - Lima, Pâmela Aparecida de (2015)
Bluetongue (BT) is a viral disease transmitted by vectors of the genus Culicoides. In Brazil, the identification of antibodies against the virus has been held for over thirty years, howeverclinicopathological diagnosis of the disease are scarce. This study describes the clinicopathological changes in sheep with BT in Minas Gerais, Brazil . In a flock of 80 male sheep 28 died. They showed clinical signs of pneumonia, anemia, and hypoproteinemia. At necropsy, the main changes observed were cranioventral lung consolidation and, hemorrhage at the base of the pulmonary artery. The histological changes consisted of bacterial bronchopneumonia and hyaline and flocculate necrosis in skeletal and cardiac muscle fibers were also observed,, associated with moderate mononuclear inflammatory infiltrate between fibers and around blood vessels. The diagnosis of BT was confirmed by the identification of nucleic acids of the virus in blood samples and from tissues of animals from the herd by RT-PCR and by the detection of antibodies against Bluetongue virus with the agar gel immunodiffusion (AGID) test using serum samples from the remaining herd animals.The objective of this study is to describe the first case of clinical LA in a sheep flock of southern Minas Gerais. The necropsy and histopathology associated with viral isolation and typing allowed the confirmation of LA in sheep. The occurrence of seropositive animals to the virus, showing that the disease may be occurring imperceptibly in sheep herds in the region.